PERAN PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK GENERASI ANTI KORUPSI DI ERA DIGITAL - Rismayanti, Dian (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
Corruption is a critical issue that undermines social order and threatens the nation's future, especially in the digital era marked by a moral crisis and the decline of honesty among the younger generation. This paper aims to examine the role of Islamic Religious Education in shaping an anti-corruption generation through the internalization of Islamic values such as honesty (?idq), trustworthiness (amanah), justice, and responsibility. The benefit of this paper is to provide both theoretical and practical foundations for educational institutions and society in implementing anti-corruption education based on religious values. This study employs a qualitative approach with a library research method, analyzing relevant literature related to Islamic education and corruption prevention. The findings indicate that integrating Islamic values into both formal and non-formal curricula—supported by the roles of teachers, families, and the use of digital technology—is effective in developing students' spiritual awareness and integrity. Islamic Religious Education proves to be a moral pillar that complements legal approaches in the comprehensive and sustainable effort to prevent corruption. ABSTRAKKorupsi merupakan persoalan krusial yang merusak tatanan sosial dan mengancam masa depan bangsa, terutama di era digital yang ditandai dengan krisis moral dan kemerosotan nilai kejujuran di kalangan generasi muda. Tulisan ini bertujuan untuk mengkaji peran pendidikan Agama Islam dalam membentuk generasi antikorupsi melalui internalisasi nilai-nilai keislaman seperti kejujuran (?idq), amanah, keadilan, dan tanggung jawab. Manfaat dari tulisan ini adalah memberikan landasan teoritis dan praktis bagi lembaga pendidikan dan masyarakat dalam menerapkan pendidikan antikorupsi berbasis nilai religius. Penelitian ini menggunakan pendekatan kualitatif dengan jenis studi pustaka, menganalisis literatur yang relevan terkait pendidikan Islam dan pencegahan korupsi. Hasil kajian menunjukkan bahwa integrasi nilai Islam dalam kurikulum formal dan nonformal, didukung peran guru, keluarga, serta pemanfaatan teknologi digital, efektif dalam membentuk kesadaran spiritual dan integritas siswa. Pendidikan Agama Islam terbukti menjadi pilar moral yang mampu melengkapi pendekatan hukum dalam upaya pencegahan korupsi secara menyeluruh dan berkelanjutan.